(untitled) (The Pretoria Student Law Review, 2021)
The creation of South Africa was accompanied by the creation of an education system that would reflect Eurocentric ideologies, concepts, and livelihoods. When South Africa attained ‘democracy’, this creation was not abolished. A direct consequence of this was that the racial epistemology of conquest continues. The #feesmustfall and #FreeDeclonisedEducation protests were a response to the persistence of this creation. However, these calls were also not realised. Which means that the racial epistemology of conquest persists. In this article I attempt to show how the realisation of these calls could have dealt with the challenges that the education system and sector faces as a result of the coronavirus pandemic. I do this by problematising the exclusionary nature of the type of education and learning that is prevalent in South Africa. I opine that in order for the racial ontology of conquest to be abolished, there should be free and decolonised education.